[OP.4B.09] CARDIAC ORGAN DAMAGE IN HYPERTENSIVE PATIENTS ACCORDING TO ON-TREATMENT BLOOD PRESSURE VALUES. (September 2016) - Salvetti, M.; Paini, A.; Rosei, C. Agabiti; Bertacchini, F.; Stassaldi, D.; Rubagotti, G.; Maruelli, G.; Verzeri, L.; Donini, C.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: The recent results of the SPRINT study suggest that "intensive" reduction of systolic blood pressure (BP) (to less than 120 mmHg) might provide greater cardiovascular protection as compared to less intensive (<140 mmHg) reduction of BP, at least in some subsets of patients. Only few studies, have investigated the possible effect of tight blood pressure control on indices of left ventricular hypertrophy, and have been mainly based on electrocardiography. Aim of our study: was to evaluate cardiac organ damage according to "on treatment" blood pressure values in a large cohort of hypertensive patients undergoing echocardiography (2D, M-mode with conventional and tissue Doppler analysis) at the echo-lab of an ESH Excellence Centre in Italy. Design and method: The analysis included 976 treated hypertensive patients (43% female, age 59 ± 12 yrs, age range 15–90). Patients were subdivided in three groups according to BP values at the time of the echocardiogram, defined as follows: uncontrolled (UC; SBP >or equal to 140 mmHg), controlled <140 (C140; SBP between 139 and 120 mmHg) and controlled <120 (C120; SBP <120 mmHg). Results: In 407 patients (42%) SBP values were >140 mmHg, 449 patients (46%) had SBP was between 139 and 120 mmHg (C140) and in 120 (12%) SBP was <120 mmHg (C120). Left ventricular mass (LVM) and LVM index (LVMI) were progressively lower in UC, C140 and C120 (LVM: 162 ± 51, 159 ± 47 and 149 ± 44 gr respectively, p for trend <0, 001; LVMI: 40 ± 11, 38 ± 10 and 35 ± 9 gr/m2.7 respectively, p for trend <0, 001). No significant difference was observed for relative wall thickness. Left atrial volume (LAV) and LAV/BSA were progressively lower in UC, C140 and C120 (LAV/BSA: 25.6 ± 7.6, 23.7 ± 7.9, 22.7 ± 8.5, respectively, p for trend <0, 001). These differences remained significant even after adjusting for possible confounders. Conclusions: Lower achieved BP targets are associated with a progressive lower left ventricular mass, left ventricular mass index and left atrial volumes. These findings are in line with previous results indicating a favorable effect of tight BP control on electrocardiographic indices of LV hypertrophy. Prospective studies are needed to confirm the possible favorable effect of tight BP control on echocardiographic indices of LVH, and their relation to CV events.